NMR-based metabolomics reveals effect of Ganoderma boninense infection on oil palm leaf at 30 days post-infection - Isha, Azizul; Yusof, Nor Azah; Abdullah, Siti Nor Akmar; Wong, Mui Yun; Osman, Rosiah (Southern Cross Publishing, 2020)
Basal stem rot is the major disease in oil palm industry that caused by a fungal named Ganoderma boninense (G. boninense) species. Infected palms are symptomless at the early stage of this disease which imposes difficulties in detecting the disease. Therefore, this study was carried out to obtain the 1 H NMR metabolomic profiling of both non-infected and G. boninense infected oil palm leaf at 30 days post-infection (dpi). This combination has provided a rapid approach in investigating the changes in the compound variations of non-infected and G. boninense infected oil palm leaf. Non-infected and G. boninense infected oil palm leaf at 30 dpi was extracted using aqueous methanol (methanol: water, 80: 20 v/v). The crude extracts obtained were analyzed by 1 H NMR-based metabolomics approach. Analysis of metabolomics data from 1 H NMR was conducted by multivariate data analysis of principal component analysis (PCA). Significant differences were found between the two groups. Compared to the non-infected leaf, the G. boninense infected leaf had higher relative abundance of choline, asparagine, alanine, succinic acid, gallic acid, epicatechin, trimethylamine, N-acetylglucosamine, N-acetyltyrosine, β-sitosterol, 2,3-butanediol, lactic acid, caffeic acid, phydroxybenzoic acid, α-tocopherol, β-cryptoxanthin and kaempferol. The non-infected leaf showed higher level of sucrose, xylose, α-glucose, S-sulfocysteine and indole-3-acetic acid. NMR-based metabolomics applied in this study reveals that G. boninense alters a manifold of primary and secondary compounds in oil palm leaf.